Anionically modified N-(alkyl)acrylamide-based semi-IPN hybrid gels reinforced with SiO2 for enhanced on–off switching and responsive properties - Kalkan, Birgul; Orakdogen, Nermin (Royal Society of Chemistry (RSC), 2022)
Semi-interpenetrated poly(N-isopropylacrylamide-co-methacrylic acid)/polyacrylamide P(NIPA–MA)/PAAm hybrids reinforced with silica were designed by incorporation of PAAm chains by simultaneous radical polymerization under warm and cold conditions.
Keywords: Acrylamide; Acrylamides; Polymers; Hydrogels; Silicon Dioxide